MAGNETIC COUPLING IN FE/CR/FE SANDWICH STRUCTURES DIRECTLY OBSERVED BY POLARIZED NEUTRON REFLECTION - Bland, J; Bateson, R; Johnson, N; Blundell, S; Speriosu, V; Metin, S; Gurney, B; Penfold, J (1993)
We have used polarised neutron reflection to directly determine the vector orientation of the individual Fe layer average magnetisations in an antiferromagnetically coupled 50 ÅFe/15 ÅCr/50 ÅFe sandwich structure prepared by sputtering. The spin dependent neutron wave in the multilayer structure is represented by a two component spinor and the resulting reflected intensity is found to be highly sensitive to variations in the orientations of the layer-dependent magnetisation vectors, permitting the preferred orientation of the average magnetisation in each Fe layer to be studied. The saturated state is found to correspond to a uniform ferromagnetic alignment of the Fe layer magnetisations. At low field, we are able to assess the degree to which the magnetic alignment is fully antiparallel, and conclude that our results are consistent with the development of a multidomain structure. © 1993.